Legal Protection for Persons with Disabilities Due to Work Accidents After the Job Creation Law - Quraisyta, Nabilla Farah; Rafiqi, Ilham Dwi (Fakultas Hukum Universitas Hang Tuah, 2023)
The legislative controversy over the Job Creation Law and its dynamics reached Law no. 6/2023 produces problematic norms. One of the problematic norms in the Employment cluster is Article 154A paragraph (1) letter m of the Law No. 6/2023 which regulates termination of employment if a worker experiences prolonged illness or disability due to a work accident. This article aims to review the conflict between these norms and other norms as well as legal protection measures for workers with disabilities due to work accidents. The research method used is normative legal research with a statutory and conceptual approach. The research results found that Article 154A paragraph (1) letter m of the Law No. 6/2023 conflicts or is disharmonious internally, horizontally and vertically with other regulations, such as the Employment Law (Law No. 13/2003), the Law on Persons with Disabilities (Law No. 8/2016), to the Indonesia Constitution 1945. The legal protection that can be carried out is first by making existing changes to the norms a quo and more repressive protection will probably be carried out because this regulation has come into effect, such as assistance, advocacy and providing free legal aid to workers with disabilities resulting from work accidents who have had their employment terminated.